Adipose tissue-derived neurotrophic factor 3 regulates sympathetic innervation and thermogenesis in adipose tissue - Xin Cui; Jia Jing; Rui Wu; Qiang Cao; Fenfen Li; Ke Li; Shirong Wang; Liqing Yu; Gary Schwartz; Huidong Shi; Bingzhong Xue; Hang Shi (Nature Communications, 2021)
Activation of brown adipose tissue thermogenesis increases energy expenditure and promotes weight loss in mice. Here the authors identify neurotrophic factor neurotrophin 3 (NT-3) as an adipokine that regulates sympathetic nervous system growth and innervation in adipose tissue and increases white adipose beiging.